The mortality of chronic kidney disease in Chinese subjects: a 12-year cohort based on clinical data in electronic health record - Qingyu Niu; Mei Hao; Mi Wang; Zhun Sui; Li Zuo (Annals of Medicine)
Background Chronic kidney disease (CKD) is a global health problem with increasing prevalence. The objective of this study was to investigate the CKD mortality rate in a large cohort study based on electronic health record (EHR).Methods This was a retrospective cohort based on Hospital’s EHR. The follow-up period was from January 2008 to December 2019. We used demographics, laboratory tests, comorbidities and mortality information to do the analysis. The mortality data was gained from the Chinese Center for Disease Control and Prevention (CDC) database. Then the data was analyzed in the whole participants and subgroups.Results 82,684 CKD patients were identified in final cohort. Overall, there were 10,454 patients who died during the 12-year follow-up. The crude mortality rate was 12.6% (2.4 per 100 patient-years). In CKD stages 4–5, the mortality rate significantly increased (10.2 and 8.8 per 100 patient-years, respectively). The major causes of death including cardiovascular diseases, infections and cancer. In the advanced (stages 4–5) CKD, the proportion of deaths caused by cancer significantly decreased (15–26% to 9–10%), while the proportion of deaths caused by renal failure markedly increased (2–4% to 10–21%). In the death group, patients with younger baseline age have a higher proportion of reaching ESRD before death: among patients with baseline age ≤35 years, for example, the percentage who died with ESKD was 28.8%, and the percentage of died with ESKD in patients with baseline age >80 years was only 14.9%.Conclusion In conclusion, among the 82,684 CKD patients, the mortality rate was 2.4 per 100 patient-years. For advanced CKD patients, the mortality rate was significantly increased. As CKD progressed, deaths caused by cancer significantly decreased, while death caused by renal failure remarkably increased. Meanwhile, there may be a competing risk of all-cause mortality and progression to ESKD.